IMPLEMENTASI KEBIJAKAN PENYEDIAAN DAN PENDISTRIBUSIAN LIQUEFIED PETROLEUM GAS 3 KG DI KABUPATEN MINAHASA SELATAN - Suoth, Lingkan; LIANDO, DAUD; Tasik, Femmy (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: the provision and distribution of Liquefied Petroleum Gas 3 KG in its implementation did not occur as policy. Many of the problems seen on void stock, hoarding, price differences and patterns of distribution are not well-ordered. This research was conducted for the purpose of analysing the implementation of the policy of distribution of Liquefied Petroleum Gas 3 KG in South Minahasa Regency in academic development resource management development in particular in the interest of the public administration management. By using qualitative design, researchers concluded that the implementation of the policy of distribution of Liquefied Petroleum Gas3 KG in South Minahasa Regency have not run well on this aspect of idealised policy, target groups, implementing organization and the environmental factor. Keywords: Implementation Of Policy, The Provision, The Distribution Of Liquefied Petroleum Gas,.